El giro populista de El Salvador: la presidencia de Nayib Bukele (2019-2023) - Nicolas Balutet (Confluenze)
This article analyzes the first presidency of Nayib Bukele who, in 2019, won the presidential elections in El Salvador, putting an end to the political alternation of the two large parties that emerged from the Chapultepec peace agreements in 1992. It attempts to show that the new president follows in the footsteps of populist rulers. To do this, this work is based on three major characteristics present in this type of regimes: the opposition between elites and the people, the control of all powers and social interaction.